System finansowania przedsiębiorstw przemysłu terenowego w całokształcie zasad systemu finansowego - Gajl, Natalia (Wydział Prawa i Administracji UAM, 1966)
The origines of the financial system of regional enterprises in Poland go back to 1950, when the former regional autonomous authorities have been transformed into regional councils of state authorities, to which have been subordinated numerous enterprises of a local field of activities (they comprise inter alia the former communal enterprises). , The principles of the financial system of regional enterprises resemble to a great extent those which govern the financial system of centrally administered enterprises. In the period of progressing regional decentralization after 1956 there are visible signs of divergences between the two systems. The motives of said divergences have their roots neither in economic discussions nor in legal premisses of state enterprises. The corporations of regional enterprises differ substantially from corporations of centrally administered enterprises — the former include enterprises of different branches and even some budgetary enterprises, and finally they are not the only superior authority of said enterprises. As there is no clearcut conception of a financial system of regional industrial corporations — it is difficult to trace in them the proper characteristics of an .enterprise. The changes in the financial system of regional enterprises introduced in 1966 are not of such a large scope as those in the centrally administered enterprises. Only the principles of financing the turnover means are similar in both systems. In respect to the system of financing the regional investments —the hitherto prevailing regulations have been maintained in force. But the regional budgets are not getting anymore the amortisation of the centralized regional enterprises (a special fund is now being set up, subordinated to the voivodship's national council). As a result of all this, the financial links of regional corporations with the groups of enterprises — are rather of a loose character. This finds its expression in the sharing of profits and the financing of losses, in the financing of investments undertaken by enterprises, in the clearing system of surpluses and shortages of turnover means and in the setting up and administration of a reserve fund within specific enterprises. In further evolution of the financial system a certain uniformity of forms in both types of enterprises (that is to say in regional enterprises and enterprises centrally administered) — can be expected, with a gradual growing of the role of the corporations in the financial economy of regional enterprises.